Marketing Mix Analysis at Hotel Handayani Sumedang - Desy Widiastuti; Desan Henriawan; Fadila Nurfauzia (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
This study is to analyze the focus of the problem of the marketing mix of Product, Price, Promotion and Place at Hotel Handayani Sumedang. The purpose of the study was to determine the implementation and how to overcome the problems of the marketing mix at the Hotel Handayani Sumedang. The research method used is a qualitative method approach. The sampling technique was carried out by purposive sampling technique. In this case, the informants are the owner, staff admin&finance, and receptionist of Hotel Handayani Sumedang. The research data used is the Miles and Huberman model with the following steps: data collection, data reduction, data presentation and conclusion drawing. The results showed that the marketing mix at Hotel Handayani Sumedang, product dimensions have product diversity by having three types of products and good product quality. Varied price dimensions, there is a match between price and product quality and apply regular discounts. The dimensions of promotion, easy-to-find advertising, personal selling who have good communication skills, public relations and sales promotions have not been realized. Dimensions where there is easy access that is easy to reach, visibility with the installation of billboards and business expansion will not apply. The marketing mix at the Handayani Hotel Sumedang is generally effective but it is necessary to improve the quality of the hotel in product dimensions and promotions to maximize sales in order to increase room occupancy rates